2023
DOI: 10.3390/ijms24097727
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Smoke Exposure, microRNA Expression during Human Lung Development, and Childhood Asthma

Abstract: Intrauterine smoke (IUS) exposure during early childhood has been associated with a number of negative health consequences, including reduced lung function and asthma susceptibility. The biological mechanisms underlying these associations have not been established. MicroRNAs regulate the expression of numerous genes involved in lung development. Thus, investigation of the impact of IUS on miRNA expression during human lung development may elucidate the impact of IUS on post-natal respiratory outcomes. We sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…For example, a recent study by Deny et al found that miRNA expression profiles differed between males and females during cystic fibrosis [ 6 ], while Gunay et al found significant miRNA differences between mice of different sexes in the methanol intoxication state [ 7 ]. Kahnamoui et al found that respiratory sensitivity was associated with miRNA expression levels in mice of different sexes [ 8 ]; Rosenberg et al found an association between the effects of different sexes on smoking and lung development [ 9 ]. In addition, research showed that certain miRNAs are expressed differently in different sexes during fetal development [ 10 , 11 ], which, in turn, results in different developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study by Deny et al found that miRNA expression profiles differed between males and females during cystic fibrosis [ 6 ], while Gunay et al found significant miRNA differences between mice of different sexes in the methanol intoxication state [ 7 ]. Kahnamoui et al found that respiratory sensitivity was associated with miRNA expression levels in mice of different sexes [ 8 ]; Rosenberg et al found an association between the effects of different sexes on smoking and lung development [ 9 ]. In addition, research showed that certain miRNAs are expressed differently in different sexes during fetal development [ 10 , 11 ], which, in turn, results in different developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…Wieczfinska and Pawliczak [15] in turn investigated signaling pathways and transcription regulation involved in airway remodeling in connection with rhinoviral infection. In addition, Rosenberg and coworkers [16] analyzed the effects of prenatal smoke exposure on microRNA expression in fetal lung and their effects on susceptibility to later development of asthma and allergies, while Kaczy ńska et colleagues [17] comprehensively summarized current knowledge on the role of regulatory peptides in asthma.…”
mentioning
confidence: 99%